NUGGET IKAN DAN DIMSUM IKAN SAYUR MENGATASI STUNTING DAN WASTING - Dewi, Zulfiana; Sajiman; Syainah, Ermina; Mas'odah, Siti; Magdalena; Andres, Mailla Dwi; Yanti, Rusmini; Rahmani; Hariati, Niken Widyastuti; Emelia, Herizka Risty; Fathurrahman; Nisa, Nurun (UPPM Poltekkes Kemenkes Banjarmasin, 2024)
Stunting, often called stunting, is a condition of failure to grow in children under five years old (toddlers) due to chronic malnutrition and recurrent infections, especially during the First 1,000 Days of Life (HPK), namely from the fetus to a 2-year-old child. Other studies show that the problem of stunting in Indonesia is related to food consumption, namely the low consumption of food sources of animal protein that are consumed daily. Data from the Food and Agriculture Organization of the United Nations (FAO) shows that consumption of animal protein per day in Indonesia is 20.30 grams, lower than other ASEAN countries such as Malaysia, Brunei, the Philippines, and Thailand. This community service activity takes the form of education about animal protein to prevent stunting and a cooking demonstration on fish nuggets and vegetable fish dim sum. The target group is cadres and mothers of toddlers in the working area of the East Martapura Community Health Center, Banjar Regency, South Kalimantan Province. The results of this community service activity show an increase in knowledge about stunting and how to prevent it.